Right heart size and right ventricular reserve in pulmonary hypertension: impact on management and prognosis - Grünig, Ekkehard; Eichstaedt, Christina; Seeger, Rebekka; Benjamin, Nicola (Diagnostics, 2020)
Various parameters reflecting right heart size, right ventricular function and capacitance have been shown to be prognostically important in patients with pulmonary hypertension (PH). In the advanced disease, patients suffer from right heart failure, which is a main reason for an impaired prognosis. Right heart size has shown to be associated with right ventricular function and reserve and is correlated with prognosis in patients with PH. Right ventricular reserve, defined as the ability of the ventricle to adjust to exercise or pharmacologic stress, is expressed by various parameters, which may be determined invasively by right heart catheterization or by stress-Doppler-echocardiography as a noninvasive approach. As the term “right ventricular contractile reserve” may be misleading, “right ventricular output reserve” seems desirable as a preferred term of increase in cardiac output during exercise. Both right heart size and right ventricular reserve have been shown to be of prognostic importance and may therefore be useful for risk assessment in patients with pulmonary hypertension. In this article we aim to display different aspects of right heart size and right ventricular reserve and their prognostic role in PH.